Situações prioritariais na enfermagem em cancerologia: modelo assistencial - Zanchetta, Margareth Santos (1990)
This is a quality matter material, that uses the contents analysis method and develops an original assistance model to deal with priority situations in the cancerology nursery area, based on the nursery theory by Roy, Orem, Levine, Peplau and Roper. The model has been built based on the experience by the author and other nurses.It consists of seven components and their features concerning to the nursery prescription basic actions. This is an important contribution for changing the assistance practice, by switching its main point from the illness to the client.